Potential ecosystem services and disservices of arthropods associated with Cyclopia (Honeybush) species. - Slabbert, Eleonore Louise (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScConsEcol)--Stellenbosch University, 2016.